Psychologist's guide to adolescents and social media - Court, Pierre (Academic Press, 2021)
The internet has become a principal venue for social interaction. Young people are growing up in a world surrounded by technology that could have only been imagined a generation ago. Social media have crafted a landscape that has made connection with others easy. Yet this rise has become a concern. So, what is happening here? Why is it so compelling to use social media? Why is it difficult to quit social media? What impact can social media have on teenagers, their education, and their well-being? Should we be worried? What can be done to help? Psychologist's Guide to Adolescents and Social Media aims to deliver a deeper understanding regarding the psychology of social media, both positive and negative. This guide is divided into four parts. The reader will be guided through the purposes and merits of social media, the unintended consequences of using social media, author conducted research exploring the experiences of adolescent-aged school children, and what can be done to help those struggling with the overuse of social media, including assessment resources.